Human Trafficking: Fighting the Illicit Economy with the Legitimate Economy - Shelley, Louise I. (Social Inclusion, 2015)
Since the beginning of research on human trafficking, there has been attention paid to the challenges surrounding the illicit economy. In creating new strategies and initiatives on combatting human trafficking, there needs to be more discussion surrounding the legitimate economy and how the business sector can make an impact in the fight against trafficking. Currently, there is a growing movement of businesses that are looking to address human trafficking through training, education, and leadership initiatives; codes of conduct; supply chain management; and financial analysis. This paper will examine the latest in these strategies and approaches by businesses in the global war against human trafficking, in addition to a discussion of a new initiative engaging the private sector co-led by Dr. Louise Shelley and Christina Bain through the World Economic Forum’s Global Agenda Council Network.